(untitled) (Health Renaissance, 2013)
Background: Breast cancer is the most common malignancy after non-melanoma skin cancers and second highest cause of cancer deaths (after lung cancer) in females. Objective: To assess racial difference of breast cancer in patients presenting to a tertiary care hospital serving indigent population. Methods: Medical records of 119 Caucasians and 146 African American women with pathologically proven breast cancer who were admitted in a tertiary care hospital serving the indigent population from January 2004 to December 2006 were reviewed retrospectively. Analysis of Variance was performed for within and between group differences using SPSS 19. Results: Our study showed that mean age of cancer diagnosis was much earlier (47.6 years) in white women whose second degree relatives have breast cancer than those women whose first degree relatives have breast cancer (58.6 years). However, in the black women this differencewas not observed (p value for white is 0.002 but for black it was 0 .94). Conclusion: Family history of women with breast cancer in this study showed history of breast cancer in a second degree female relative increased the risk of breast cancer in white women; positive history was associated with earlier age of onset of the disease. We suggest future studies should look into genetic and biological markers in the second generation family members for increased risk of breast cancer. Health Renaissance, January-April 2013; Vol. 11 No.1; 102-106 DOI: http://dx.doi.org/10.3126/hren.v11i2.8215